Can an educational podcast improve the ability of parents of primary school children to assess the reliability of claims made about the benefits and harms of treatments: study protocol for a randomised controlled trial - Semakula, Daniel; Nsangi, Allen; Kaseje, Margaret; Sewankambo, Nelson K. (Trials, 2017)
Claims made about the effects of treatments are very common in the media and in the population more generally. The ability of individuals to understand and assess such claims can affect their decisions and health outcomes. Many people in both low- and high-income countries have inadequate aptitude to assess information about the effects of treatments. As part of the Informed Healthcare Choices project, we have prepared a series of podcast episodes to help improve people’s ability to assess claims made about treatment effects. We will evaluate the effect of the Informed Healthcare Choices podcast on people’s ability to assess claims made about the benefits and harms of treatments. Our study population will be parents of primary school children in schools with limited educational and financial resources in Uganda.